Integrasi SIG dalam Analisis Kepadatan Penduduk di Desa Limau Manis, Desa Medan Sinembah, dan Desa Ujung Serdang - Fatimah Azzahra; Regita Asiah Azzarah; Muhammad Alfi Harahap; Sara Enjelina Sianipar; Ridho Amalan Saufi Sipahutar (JPIG (Jurnal Pendidikan dan Ilmu Geografi), 2025)
This study aims to analyze the population density in Limau Manis Village, Medan Sinembah Village, and Ujung Serdang Village in Tanjung Morawa District, Deli Serdang Regency, using a qualitative approach. The research problem is to understand the factors influencing the distribution of population density in these three villages. The methods used include primary data collection through surveys and interviews with village officials and local communities, as well as secondary data collection from planning documents and village maps. Data analysis was performed using thematic analysis techniques and spatial data integration using Geographic Information Systems (GIS). The results show that Limau Manis Village has the highest population (23,083 people) due to good accessibility, adequate public facilities, and greater economic opportunities. Medan Sinembah Village has a population of 9,242 people, with density variations influenced by access to natural resources and infrastructure. Ujung Serdang Village has the lowest population (5,086 people) due to challenging geographical conditions and limited public facilities. The recommendation of this study is to improve infrastructure and public facilities in low-density villages to enhance the quality of life and balance the population distribution.